2020
DOI: 10.3390/jmse8100781
|View full text |Cite
|
Sign up to set email alerts
|

Marine Snow Aggregates are Enriched in Polycyclic Aromatic Hydrocarbons (PAHs) in Oil Contaminated Waters: Insights from a Mesocosm Study

Abstract: Marine snow was implicated in the transport of oil to the seafloor during the Deepwater Horizon oil spill, but the exact processes remain controversial. In this study, we investigated the concentrations and distributions of the 16 USEPA priority polycyclic aromatic hydrocarbons (PAHs) in marine snow aggregates collected during a mesocosm experiment. Seawater only, oil in a water accommodated fraction (WAF), and Corexit-enhanced WAF (DCEWAF) were incubated for 16 d. Both WAF and DCEWAF aggregates were enriched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 94 publications
2
8
0
Order By: Relevance
“…One clear pattern that emerged from this analysis, however, is the depletion of naphthalene and fluorene in nearly all the marine snow and the sediment samples relative to the composition of the original Macondo oil and the surrogate oil used in the roller table and mesocosm experiments. This is not surprising, as studies have shown rapid depletion and degradation of water soluble, light, volatile, low-molecular weight PAHs such as naphthalene and fluorene (Kappell et al, 2014;Bacosa et al, 2020). Overall, this analysis shows that the marine snow formed in the laboratory experiments such as roller table and mesocosm experiments closely mimicked the material found to be sedimenting in the field, further underscoring the role of MOSSFA phenomena during the DwH oil spill.…”
Section: How Does the Presence Of The Resulting Ternary System (Oil-dispersant-eps) Modify The Fate Of The Oil?supporting
confidence: 62%
See 3 more Smart Citations
“…One clear pattern that emerged from this analysis, however, is the depletion of naphthalene and fluorene in nearly all the marine snow and the sediment samples relative to the composition of the original Macondo oil and the surrogate oil used in the roller table and mesocosm experiments. This is not surprising, as studies have shown rapid depletion and degradation of water soluble, light, volatile, low-molecular weight PAHs such as naphthalene and fluorene (Kappell et al, 2014;Bacosa et al, 2020). Overall, this analysis shows that the marine snow formed in the laboratory experiments such as roller table and mesocosm experiments closely mimicked the material found to be sedimenting in the field, further underscoring the role of MOSSFA phenomena during the DwH oil spill.…”
Section: How Does the Presence Of The Resulting Ternary System (Oil-dispersant-eps) Modify The Fate Of The Oil?supporting
confidence: 62%
“…A comparison of PAH composition in MOS from laboratory roller table (Genzer et al, 2020) and mesocosm experiments [Bacosa et al, 2020;and GRIIDC dataset (10.7266/ER1EGZ8E)] with the PAH composition examined in the sediment samples of Gulf of Mexico (Romero et al, 2015), revealed interesting findings (Figure 5). Using non-metric multidimensional scaling (NMDS), the data points of both WAF and DCEWAF from roller table and mesocosm experiments clustered together with the sediment samples, suggesting some level of consistency in the PAHs that tend to remain in marine snow.…”
Section: How Does the Presence Of The Resulting Ternary System (Oil-dispersant-eps) Modify The Fate Of The Oil?mentioning
confidence: 98%
See 2 more Smart Citations
“…The BRTs were used by Doyle et al (2018) in mesocosm experiments designed to study the relationship among microbial community structure, oil and Corexit, and MOS in coastal surface waters; by Bacosa et al (2020) to investigate the concentration and distribution of hydrocarbons in marine snow aggregates; and by Shi et al (2020) to determine the half-lives of individual hydrocarbons in simulated oil spill scenarios with and without dispersant.…”
Section: Sample Volumementioning
confidence: 99%